KEANEKARAGAMAN SERANGGA PADA PERTANAMAN KACANG PANJANG (Vigna sinensis L) DI DESA SUMBERARUM KECAMATAN NGRAHO KABUPATEN BOJONEGORO - Muamalah, Dwi Nurfiana; Nasirudin, Mohammad; Na’im, Abu (Jurnal Agriovet, 2024)
Long beans (Vigna sinensis L.) are a type of vegetable crop that has been cultivated for a long time and is one of the plants that are widely consumed by the people of Indonesia One of the barriers to the productivity of long beans is pest attacks. One of the efforts made by farmers to control pests is by using insecticides. Conventional pest control began to be abandoned and switched to control based on the concept of PHT to reduce the negative impact of the use of pesticides by using yellow trap trap media. This study aims to determine the diversity of insects, this study identifies insects on long bean farmland that are interested in the color of traps that have been installed in 5 places systematically. The diversity of insects found in this study is 20 families. It consists of Chrysomelidae, Coccinellidae, Scarabidae, Reduvidae, Alydidae, Satyridae, Blattellidae, Tachinidae, Agromyzidae, Drosophildae, Tephritidae, Muscidae, Acrididae, Ichneumonidae, Formicidae, Braconidae, Cicadellidae, Aphididae, Pyralidae, and Pentatomidae. The value of the insect diversity index (H') in semi organic is 2.50 and anorganic is 2.58. The dominance on semi organic is 0.101 and anorganic is 0.103 which means low. This shows that the land has a variety of insect species and no insect species dominate.